2005
DOI: 10.1007/s10194-005-0249-z
|View full text |Cite
|
Sign up to set email alerts
|

Clinical efficacy of rizatriptan for patients with migraine: efficacy of drug therapy for migraine accompanied by tension headache–like symptoms, focusing on neck stiffness

Abstract: According to an epidemiological study in Japan, there are as many as 22 million patients with tension headache and 8.4 million with migraine. Furthermore, patients suffering from both types of headache concurrently are estimated to account for more than 50% of headache patients. We studied the efficacy of drug therapy for migraine accompanied by tension headache-like symptoms, focusing principally on neck stiffness. We evaluated the efficacy of rizatriptan by comparison of findings before and after therapy in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 13 publications
1
8
0
Order By: Relevance
“…It is also noteworthy that the current study has shown the involvement of purinergic receptor mechanisms specifically in duraevoked neck muscle activity, consistent with previous findings of P2X receptors in the dura and MDH [10,11, 21], and, as noted above, of the involvement of MDH as an interneuronal site in trigeminally evoked neck muscle reflex pathways [1]. Thus, it is also possible that P2X receptor mechanisms in the dura and MDH may play an important role in neck stiffness, which is a common symptom of migraine and other types of headaches [1820]. …”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…It is also noteworthy that the current study has shown the involvement of purinergic receptor mechanisms specifically in duraevoked neck muscle activity, consistent with previous findings of P2X receptors in the dura and MDH [10,11, 21], and, as noted above, of the involvement of MDH as an interneuronal site in trigeminally evoked neck muscle reflex pathways [1]. Thus, it is also possible that P2X receptor mechanisms in the dura and MDH may play an important role in neck stiffness, which is a common symptom of migraine and other types of headaches [1820]. …”
Section: Discussionsupporting
confidence: 88%
“…application to the medulla of TNPATP or the NMDA receptor antagonist APV can also block the increase in neck muscle EMG activity evoked by α,β-meATP application to the dura. Since ATP and glutamate are associated with some headache conditions [24] and neck muscle stiffness has been reported to occur with dura inflammation in migraine headache [18], tension-type headache [19] and meningitis [20], these novel findings suggest that some headache conditions may involve afferent inputs into the central nervous system that utilize dural purinergic processes and that are modulated by medullary purinergic and NMDA receptor mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…As expected by the investigators, rizatriptan provided good efficacy in the general study population (79.4% pain relief and 41.2% pain-free at 2 h). Pain relief in patients without neck stiffness (56.3% pain free at 2 h) was superior to that in patients who had neck stiffness (27.8% pain free at 2 h) and patient satisfaction was also observed as better in patients who did not have neck stiffness [45] .…”
Section: Rizatriptan For Other Symptoms Accompanying Migrainementioning
confidence: 92%
“…It has been estimated that > 50% of headache patients experience both migraine and tension headache [45,46] . Sumatriptan has been shown in some studies to be effective in alleviating both migraine and tension-like headache features; in a recent study among patients with self-reported tension headache who met criteria for migraine, sumatriptan did not differ from placebo in terms of pain relief at 2 h but provided effective relief at 4 h and sustained relief at 24 h [46] .…”
Section: Rizatriptan For Other Symptoms Accompanying Migrainementioning
confidence: 99%
See 1 more Smart Citation